1989
DOI: 10.1021/ja00205a050
|View full text |Cite
|
Sign up to set email alerts
|

Radical cation Cope rearrangement of 1,5-hexadiyne to 1,2,4,5-hexatetraene (bis(allene)) at 77 K

Abstract: 23) N62H cytochrome c (50 mg) was reacted with a 40-fold excess of [a5Ru(H20)](PF6)2 (80 mg, 0.16 mmol) in 16 mL of deoxygenated HEPES, pH 7.0, for 45 min in an argon atmosphere. The reaction was terminated by separating the protein from the unreacted ruthenium complex on a Sephadex G-25 column. The protein was oxidized with [CoEDTA]" prior to FPLC purification.(24) Mocera, D. G.; Winkler,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The Cope rearrangement is an example of a reaction that can be promoted by oxidation. Simple ionization energy estimates predict that the radical cation Cope rearrangement should have an “inverted” potential energy surface, wherein the cyclic geometry that corresponds to the transition state for reaction of the neutral diene is an intermediate (Figure ). Thus, matrix isolated 1,5-hexadiene radical cation generated by pulse radiolysis spontaneously cyclizes to the cyclohexane-1,4-diyl radical cation. , Consequently, Ikeda et al have used photoinduced electron transfer to afford the cyclization of a phenyl-substituted hexadiene derivative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cope rearrangement is an example of a reaction that can be promoted by oxidation. Simple ionization energy estimates predict that the radical cation Cope rearrangement should have an “inverted” potential energy surface, wherein the cyclic geometry that corresponds to the transition state for reaction of the neutral diene is an intermediate (Figure ). Thus, matrix isolated 1,5-hexadiene radical cation generated by pulse radiolysis spontaneously cyclizes to the cyclohexane-1,4-diyl radical cation. , Consequently, Ikeda et al have used photoinduced electron transfer to afford the cyclization of a phenyl-substituted hexadiene derivative.…”
mentioning
confidence: 99%
“…The Cope rearrangement is an example of a reaction that can be promoted by oxidation. [21][22][23][24] Simple ionization energy estimates predict that the radical cation Cope rearrangement should have an "inverted" potential energy surface, 21 wherein the cyclic geometry that corresponds to the transition state for reaction of the neutral diene is an intermediate (Figure 1). Thus, matrix isolated 1,5hexadiene radical cation generated by pulse radiolysis spontaneously cyclizes to the cyclohexane-1,4-diyl radical cation.…”
mentioning
confidence: 99%
“…A shock-tube pyrolysis study of 2 in the temperature range of 540 to 1180 K at two nominal pressures (22 and 40 kbar) revealed that 2 plays an important role in the so-called propargyl mechanism, which is of importance in relation to the formation of aromatic compounds from nonaromatic precursors [112]. A radical cation Cope rearrangement of 1,5-hexadiyne ( 129 ) to the 1,2,4,5-hexatetraene radical cation was initiated by oxidizing bipropargyl radiolytically in a Freon matrix at 77 K [113]. The 129 → 2 → 130 sequence, and in particular its last step, has also been used several times for the preparation of functionalized bismethylenecyclobutenes, as demonstrated, for example, in Scheme 14.…”
Section: Reviewmentioning
confidence: 99%
“…The difficulty in completing the full Cope reaction can, however, be circumvented by installing cation radical stabilizing groups at the 3 and 4 positions of a 1,5-hexadiene derivative [94] or by providing for the delocalization of the cation radical [931. moiety of the product over a conjugated system consisting of the original C1, C2, C5, and C6 atoms (Scheme 54) [95]. Although the former case may well proceed by a stepwise, distonic cation radical, mechanism, the latter one does appear to be a bona fide example of a concerted [3,3] sigmatropic shift.…”
Section: The Cation Radical Cope Reactionmentioning
confidence: 99%